2013
DOI: 10.1186/1471-2164-14-66
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of soybean microRNAs and their targets reveals their organ-specificity and responses to phosphate starvation

Abstract: Background: Phosphorus (P) plays important roles in plant growth and development. MicroRNAs involved in P signaling have been identified in Arabidopsis and rice, but P-responsive microRNAs and their targets in soybean leaves and roots are poorly understood. Results: Using high-throughput sequencing-by-synthesis (SBS) technology, we sequenced four small RNA libraries from leaves and roots grown under phosphate (Pi)-sufficient (+Pi) and Pi-depleted (-Pi) conditions, respectively, and one RNA degradome library fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
101
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 73 publications
(149 reference statements)
12
101
4
Order By: Relevance
“…In plants, a subset of miR169 members are repressed by N and P starvation (Pant et al, 2009;Liang et al, 2012;Xu et al, 2013), and several miR169 NFYA targets are induced in such conditions (Pant et al, 2009;Zhao et al, 2011). We observed similar results in this study in wheat: low-N and low-P treatments decreased tae-miR169 abundance ( Fig.…”
Section: Nf-y Genes In Wheat Respond Variously To N and P Starvationsupporting
confidence: 78%
See 2 more Smart Citations
“…In plants, a subset of miR169 members are repressed by N and P starvation (Pant et al, 2009;Liang et al, 2012;Xu et al, 2013), and several miR169 NFYA targets are induced in such conditions (Pant et al, 2009;Zhao et al, 2011). We observed similar results in this study in wheat: low-N and low-P treatments decreased tae-miR169 abundance ( Fig.…”
Section: Nf-y Genes In Wheat Respond Variously To N and P Starvationsupporting
confidence: 78%
“…Different members of this microRNA family show distinct response patterns to N or P starvation (Pant et al, 2009;Liang et al, 2012;Xu et al, 2013). As such, miR169 and its targets may be valuable resources for engineering plants with altered N and/or P use efficiencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, members of miR399 genes contain PHR1-binding sites PIBS (GNATATNC); a motif that is required for binding to most of P-responsive genes and is critical for their transcriptional regulatory functions (Bari et al, 2006). Interestingly, other P-related cis elements such as PHR1, PHO-like, W-box, TATA-box and P-responsive elements were also found in the upstream promoter sites of P-responsive miRNAs including miR399 Xu et al, 2013). Under P deficiency, Arabidopsis phr1 mutants showed significantly reduced expressions of miR399 as well as group of other P related genes, while set of P deficiency-responsive genes were found upregulated in pho2 mutants under sufficient P availability, hence, concluded that PHR1 functions upstream of miR399 and PHO2, however, it is not the only element required for miR399 induction in P signaling network (Bari et al, 2006).…”
Section: Mirnas and Their Targets Under Limited Phosphorousmentioning
confidence: 99%
“…All miR399 genes present in Arabidopsis harbor PHR1-binding site P1BS in their promoters (Bari et al 2006 ). Also several other P-responsive cis -regulatory elements were identifi ed in the promoters of these phosphate-responsive miRNAs including PHO, PHO-like, W-box, NIT2, and MYB-binding sites (Zeng et al 2010 ;Xu et al 2013 ;Baek et al 2013 ). Further fi ndings also indicated that miR399-mediated regulation of PHO2 is under the control of target mimicry.…”
Section: Phosphate Homeostasismentioning
confidence: 92%